Modelo para priorização dos fatores críticos de sucesso, dimensões e tecnologias digitais das Fintechs a partir da indústria 4.0 - Fernandes, Carlos Henrique (2022)
Although the topic Industry 4.0 is being widely discussed in the business and academic spheres, there are still several ramifications of the technological impacts of this new revolution, especially when it comes to business typologies. The reflection of the system established by Industry 4.0 can be observed in the financial sector, which, thanks to the disruptive power of its technologies, has enabled the consolidation of a new business in the sector, called Fintech, derived from the junction of the terms technology and finance. In view of this, the present work aims to propose a model for prioritizing the Critical Success Factors, Macro Dimensions, and Digital Technologies for Fintechs in the context of Industry 4.0. To obtain the theoretical portfolio and develop the study, a systematized literature review (RBS) was developed from the PRISMA methodology, resulting in a final portfolio composed of 86 papers. To analyze the portfolio of this work, we chose to use the Nvivo [trade mark] version 10 QSR Software, through which it was possible to prepare the content analysis for the identification of the Critical Success Factors (CSF) and the characteristics of the main digital technologies and Fintechs typologies. The analysis of the portfolio resulted in 36 CSFs that were compiled into 5 dimensions being: Business Management, User Experience, Infrastructure, Technology Innovation and Value Proposition. To evaluate the level of importance of the digital technologies, macro dimensions and CSF, they were submitted to experts using the Fuzzy Delphi method, to establish the relevance of each item, enabling its prioritization. Thus, it was established that the items that obtained the best evaluation were respectively cybersecurity, user experience, and data security. Therefore, it was possible to diagnose that the main focus of Fintechs is to offer the best experience guaranteeing the security of the data obtained during the process, demonstrating that technologybased business types need to pass on all the security of the use of resources coming from technology to their clients, in order to reduce any type of insecurity.